Mesoscopic modelling of microbubble in liquid with finite density ratio of gas to liquid. (18th June 2018) - Pan, Dingyi; Zhao, Gengyao; Lin, Yuqing; Shao, Xueming
Abstract: A microbubble model is developed with the mesoscopic simulation tool, dissipative particle dynamics (DPD) and many-body dissipative particle dynamics (MDPD). Standard DPD particles are employed to represent bubble phase at low density, and MDPD particles are for the liquid phase. The microbubble can be stable in liquid, in contrast to the vacuum bubble model. Gas-liquid interface is well presented with density and pressure jumps. The density ratio of gas to liquid can be lower than 0.1 by increasing the cut-off radius of bubble particles. Oscillating behavior of the microbubble model is investigated and validated by comparing with the Rayleigh-Plesset equation. The current model shows correct dynamic response, and the fluctuating behavior is captured as well. The lower the density ratio of the microbubble model, the closer the oscillating frequency to that of continuum theory.